Architecture, form, space & order - Ching, Frank, 1943- 4 0 16; 5 (New York : John Wiley & Sons, 1996)
An illustrated, comprehensive guide to the functions of form and space in architecture, which covers primary elements, organization, circulation, proportion and scale, and ordering principles.
A VNR book.
Includes bibliographical references (p. 377) and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; Composition, proportion, etc.;Composition, proportion, etc.;Philosophy. -- Architecture;Space (Architecture);Architecture;Architecture;Perception.; 20; 2